necesidad de incorporar en el código orgánico integral penal coip ecuatoriano, una disposición normativa que regule el caso en el que el fiscal en la audiencia de juicio se abstenga de acusar al procesado ante el tribunal de garantías penales - Tapia Pinta, Wilmer Ramiro (2016)
This thesis work concerns the problems arising from the lack of procedural rules in the Code of Integral Criminal governing the case where the prosecutor in the trial hearing refrain from accusing the defendant before the court of criminal guarantees , resulting in legal practice judges and prosecutors do not have an adequate legal framework for solving this problem, thus generating affectations accusatory - adversarial principle , the principle device , principle of opportunity , principle of fairness, principle of constitutional and legal autonomy of the prosecutor accused , due process rights such as the right to a defense that includes several guarantees, legal certainty and others. Therefore, for the development of this research a review of the procedural rules relating to the trial stage of the ordinary procedure contained in the COIP was performed , as well as presented the opinion of the doctrine of the issues raised, was also made a review of procedural rules on the case proposed legislation comparative: Peru, Venezuela Chile, Colombia and Argentina, rules contained in international instruments ratified by Ecuador, and finally with the results obtained in the field research that a procedural reform the COIP determined appropriately and efficiently the rules applicable in the event that the prosecutor refrain from accusing the defendant in the trial hearing criminal court guarantees. This thesis contains a study of the social and legal reality Ecuador, as it refers to the " need to incorporate CODE ORGANIC INTEGRAL CRIMINAL COIP ECUATORIANO, a legislative provision regulating IF THE TAX IN THE HEARING OF JUDGEMENT ABSTAIN TO ACKNOWLEDGE THE PROCESSING BEFORE THE COURT OF CRIMINAL WARRANTIES. " As such therefore propose to analyze the Code of Integral Criminal promptly in the Ecuadorian criminal procedure , identifying crimes of public action , analysis of the Ordinary Criminal Procedure in its trial stage, as we give you a greater knowledge and understanding of the criminal law and allow the Public Ministry and professionals of regulations governing tax law abstention and the legal consequences it produces for the prosecution and for processing ; based on the Constitution of the Republic , international treaties relating to criminal law accepted by our country , comparative law , the Code of Integral Penal , and finally as a postulant of this thesis suggest the incorporation of a regulation governing this problem legal in criminal matters. Collection and consultation of bibliographical sources , as a methodological procedure was used to carry out this work. The theoretical and field research of this work allowed us to obtain criteria , with clear and precise foundations , well known literature , which contributed to the verification of goals , and testing of the hypotheses , enabling support the proposed changes. The content of this thesis is an intellectual effort of the applicant in the legal , scientific and methodological level, which deals theoretically and empirically , to respect the role of the prosecution in the case of abstaining accused by the prosecutor to processed before guarantees criminal court , the legal effects posed to the prosecution and processing and finally its impact on today's society.